Late Bronze Age Violin bow fibulae between Danube, central Adriatic and Aegean - Pabst, Sabine (Arheološki vestnik, 2018)
This article analyses special shapes of late Bronze Age violin bow fibulae in the area between the Danube, central Adriatic and Aegean. The investigation focuses on the typology and chronology of fibulae, the distribution of types as well as the identification of intercultural relations and social processes behind them. The distribution maps of several violin bow fibula types of Danubian or north-western Balkan origin especially indicate close cultural contacts between the Pannonian-north-western Balkan area and the Apennine peninsula across the central Adriatic Sea. In addition, Sicily and the Aegean participated in these intercultural connections. In the 13th century BC the wide distribution of violin bow fibulae was obviously connected with Mycenaean trade activities in the Adriatic. During the 12th century BC the trans-Adriatic contacts were not only restricted to violin bow fibulae but included burial practices as well as a special kind of metal deposition. Finally, in post-palatial times Mycenaean trade in the Adriatic and Ionian Sea starting from Achaia resulted in a more intensive communication between the local populations on both sides of the central Adriatic, perhaps also including smaller population movements.